Implementasi Model Pembelajaran RME Berbantuan LMS-Canva sebagai Upaya Memotivasi Siswa yang Ditinjau dari Sudut Pandang Filsafat Matematika - Rusmini Rusmini; Izwita Dewi; Elmanani Simamora (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The aim of this research is to find out whether the implementation of the Realistic Mathematics Education (RME) learning model assisted by LMS-Canva has a motivating impact on students from a mathematical philosophy perspective. This research method is qualitative. The resource persons for this research were students and teachers at SMP Negeri 3 Percut Sei Tuan. Data was obtained by observation, interviews, observations during the process of implementing the learning model in all classes VII and VIII. Conduct interviews with students and subject teachers and homeroom teachers by gathering teachers in the hall of SMP Negeri 3 Percut Sei Tuan. Provide short questions and answers to both students and teachers regarding the learning model applied. Based on triangulation of data obtained, the implementation of the RME learning model provides an overview of the RME learning model from the perspective of mathematical philosophy and the implementation of the learning model with LMS-Canva. The implementation of the RME learning model is significant in efforts to motivate students to learn mathematics.